Evidence in Administrative Sanctioning Proceedings (public school teachers) - de Vargas, María Cinta (Avances en Supervisión Educativa, 2026)
The assessment of evidence constitutes one of the fundamental procedural elements in a disciplinary sanctioning proceeding. The justification for the procedure is that the facts can be proven; once this is done, they can be subsumed under a disciplinary classification and a proportionate analysis can be carried out to determine an appropriate, balanced, and suitable sanction.The connection between evidence and the right of defense of the respondent in administrative sanctioning proceedings entails the assumption of all procedural legal guarantees. Therefore, taking into account the similarity of such proceedings to civil and criminal judicial processes, standards of assessment must be applied that respect the principles of adversarial procedure, immediacy, and publicity (with certain qualifications), as well as, as a substantive principle, the presumption of innocence, in order to safeguard the respondent’s right of defense.
Keywords: Administrative sanctioning procedure; Presumption of innocence; evidence; burden of proof; means of evidence